Answer:
Aye My Guy You Got The Answer Yet Lol
Step-by-step explanation:
False ......................................
x + 2y + 3 = 0
Subtract x from both sides.
2y + 3 = -x
Subtract 3 from both sides.
2y = -x - 3
Divide by 2 on both sides
y = -(x+3)/2
x + y + 4 = 0
Subtract x and 4 from both sides
y = -x - 4
3x - 2y + 4 = 0
Subtract 3x and 4 from both sides.
-2y = -3x -4
Divide by -2 from both sides.
y = -(3x + 4) / 2
The answer is the graph that contains these slopes and lines on the graph, which was not provided.
Answer:
3 (m^2 - 16)
Step-by-step explanation:
factoring means taking out a common multiple of all the terms in the expression
in this case, if you multiply 3 and m^2, 3 and -16, you would get 3m^2-48
so you take the three and put it outside of the parenthesis that contains the factored terms
this leaves you with 3 (m^2 - 16)